Quantitative Evaluation of China’s Pork Industry Policy: A PMC Index Model Approach - Li, Youzhu; He, Rui; Liu, Jinsi; Li, Chongguang; Xiong, Jason (Agriculture (Basel), 2021)
To ease the fluctuation of hog prices and maintain the hog market’s stability, the central government of China has issued a series of hog price control policies. This paper, supplemented by co-word analysis and LDA thematic modeling, constructed 9 first-level indicators and 36 second-level indicators and used a PMC index model to conduct quantitative research on the selected 74 policies and regulations of China’s pig price regulation policies from July 2007 to April 2020. The research concludes that the research tool system of China’s hog price control is formed. The overall design of the hog price control policy is relatively reasonable, but there are still the following problems: the subject of China’s pig price control policy is singular, so it is difficult to form a resultant force; the policy pays attention to the price regulation in the short term, but ignores the long-term industrial structure adjustment; it emphasizes market supervision, but insufficient support for slaughtering and processing; it focuses on production and management to improve the development quality and efficiency of the pig industry, but does not take social equity into account. Finally, some policy suggestions are put forward: multi-department division of labor and close cooperation; adjusting the industrial structure of hog and carrying out appropriate large-scale breeding; establishing the operation mode of slaughtering and processing in the producing area to reduce the circulation cost of the pig industry; ensuring the consumption of pork by low-income groups and giving consideration to social efficiency and equity.